The Challenge of Position-Taking in Novice Higher Education Students’ Argumentative Writing - Kleemola, Katri; Hyytinen, Heidi; Toom, Auli (Frontiers in Education, 2022)
Argumentative writing is the central generic skill in higher education studies. However, students have difficulties in basic argumentation skills. Novice students do not necessarily receive adequate guidance, and their prior education may not have supported the requirements of higher education writing. Position-taking is at the core of argumentation, but students are often hesitant to make their point. Furthermore, they may have an incorrect and one-sided perception about an argument, leading them to avoid alternative positions in their argumentative writing. The study aims to explore starting level skills of novice students’ argumentative writing, namely their position-taking. The participants were 196 first-year students from diverse fields of study in two Finnish higher education institutions. They were required to solve a problem and write an argumentative essay based on five documents that were given to them. The essays were analyzed using qualitative content analysis applying abductive approach. Substantial variation was detected in students’ position-taking. We identified four groups of writers based on their position-taking. First two groups were more or less explicit in their position-taking. Most of the students (72%) belonged to these two groups. However, a minority of them were consistent in their position-taking. Writers in the third group (15%) implied their position, and writers in the fourth group (12%) stuck to summarizing sources without position-taking. The findings invite teachers to support novice students in their basic argumentation. Co-operation between faculty teachers and writing teachers is encouraged.